2023
DOI: 10.3390/ijms241713260
|View full text |Cite
|
Sign up to set email alerts
|

GSK3α Regulates Temporally Dynamic Changes in Ribosomal Proteins upon Amino Acid Starvation in Cancer Cells

Lorent Loxha,
Nurul Khalida Ibrahim,
Anna Sophie Stasche
et al.

Abstract: Amino acid availability is crucial for cancer cells’ survivability. Leukemia and colorectal cancer cells have been shown to resist asparagine depletion by utilizing GSK3-dependent proteasomal degradation, termed the Wnt-dependent stabilization of proteins (Wnt/STOP), to replenish their amino acid pool. The inhibition of GSK3α halts the sourcing of amino acids, which subsequently leads to cancer cell vulnerability toward asparaginase therapy. However, resistance toward GSK3α-mediated protein breakdown can occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 75 publications
(139 reference statements)
0
4
0
Order By: Relevance
“…Subsequent RNA-sequencing analyses revealed that GSK3α KD cells surviving asparagine depletion were characterized by a downregulation of various ribosomal proteins (RP). Moreover, the suppression of specific RP in GSK3α KO cells was sufficient to protect them from asparaginase-induced cell death, collectively suggesting a detrimental influence of these RP on GSK3α-dependent cancer cell survival under these conditions [24]. In the next study, metabolic regulation was revisited as one of the most prominent functions of GSK3.…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…Subsequent RNA-sequencing analyses revealed that GSK3α KD cells surviving asparagine depletion were characterized by a downregulation of various ribosomal proteins (RP). Moreover, the suppression of specific RP in GSK3α KO cells was sufficient to protect them from asparaginase-induced cell death, collectively suggesting a detrimental influence of these RP on GSK3α-dependent cancer cell survival under these conditions [24]. In the next study, metabolic regulation was revisited as one of the most prominent functions of GSK3.…”
mentioning
confidence: 92%
“…The next three studies presented in this Special Issue are dedicated to the impact of GSK3 modulation on central cellular processes, i.e., cell cycle progression [23], the management of amino acid (aa) deprivation [24], and metabolism [25]. Shenker et al, for instance, were interested in elucidating the cytotoxic properties of Aggregatibacter actinomycetemcomitans-derived cytolethal distending toxin (AaCdt) [23], a heterotrimeric bacterial toxin possessing both DNase and lipid phosphatase activity, which typically causes cell cycle arrest and apoptosis [26].…”
mentioning
confidence: 99%
See 2 more Smart Citations